(p,γ) Reaction Cross Sections Relevant to the p process: First Results for the Se Isotopes - Lagoyannis, A.; Spyrou, A.; Harissopulos, S.; Galanopoulos, S.; Kunz, R.; Fey, M.; Hammer, J. W.; Julin, R.; Demetriou, P. (HNPS Advances in Nuclear Physics, 2020)
Proton-capture reaction cross sections of Se isotopes were determined in the 1-6 MeV energy range by means of γ-angular distribution measurements as well as via the activation technique. In this report we compare our first cross-section results with statistical model calculations performed using various microscopic and phenomenological approaches of Optical Model Potentials and Nuclear Level Densities.